Pengaruh Efikasi Diri dan Pengetahuan Manajemen Keuangan Bisnis Terhadap Intensi Berwirausaha - Heni Dwi Listyaningrum; Henny Kumalasari Widodo; Sulartopo Sulartopo (Journal of Management and Social Sciences, 2023)
Abstract Main problem: the influence of self-efficacy and business financial management knowledge on entrepreneurial intentions. Objective: to determine and analyze the influence of self-efficacy and business financial management knowledge on entrepreneurial intentions. Originality: the influence of self-efficacy and business financial management knowledge on entrepreneurial intentions. Method: this exploration is quantitative and is applied due to the influence of two or more factors explicitly when building a relationship. Results: self-efficacy has a positive and extraordinary impact on the desire for entrepreneurship. Knowledge of financial management influences the desire for entrepreneurship in central java.